Comparison of in-person and telegeriatric follow-up consultations. (January 2023) - Betkus, Georgia; Freeman, Shannon; Martin-Khan, Melinda; Lau, Shell; Flood, Frank; Hanlon, Neil; Banner-Lukaris, Davina
Introduction: Telehealth has the potential to support the care of older adults and their desire to age at home by providing a videoconferencing connection to specialist geriatric care. However, more information is needed to determine how telehealth services affect the care of older adults, and how telehealth services for older adults compare to traditional in-person methods of care provision. The aim of this study was to compare telegeriatric and in-person geriatric consultation methods with respect to outcomes and costs. Methods: This was a retrospective chart analysis of consultation letters from patients' first follow-up appointment with a geriatric specialist during the 2017/2018 fiscal year ( N = 95) in a health jurisdiction of a Western Canadian province. Results: Patients seen through telehealth and in person were similar in mean age ( M = 79.1 and 78.1 years, respectively) and were predominately female. Telegeriatric consultations resulted in more requests for further testing and screening ( p = 0.003), new diagnoses ( p = 0.002), medication changes ( p = 0.009) and requests for follow-up ( p = 0.03) compared to in-person consultations. An average one-day clinic with one geriatric specialist providing consultations through telehealth cost Can1684–1859 less than an equivalent in-person clinic. Discussion: Although additional research is needed to explain the differences in outcomes further between telehealth and in-person consultations found in this work, telehealth consultations cost substantially less than in-person consultations and are a promising way to improve access to geriatric care for older adults in underserved areas.